High prevalence and risk factors of fecal carriage of CTX-M type extended-spectrum beta-lactamase-producing Enterobacteriaceae from healthy rural residents of Taian, China - Zhang, Hongna; Zhou, Yufa; Guo, Shuyuan; Chang, Weishan (Frontiers in Microbiology, 2015)
The study was carried out to understand the prevalence of CTX-M type extended-spectrum beta-lactamase (ESBL)-harboring Enterobacteriaceae and to analyze risk factors related with fecal carriage in healthy rural residents in Taian, China. A total of 620 stool samples were collected from rural residents. The ESBL-positive Enterobacteriaceae was screened using ChromID ESBL agar, and then further confirmed by double-disk diffusion. The CTX-M genes were determined using polymerase chain reaction. The risk factors associated with fecal carriage of CTX-M-positive isolates were analyzed using the standard statistic methods. 458 isolates carrying CTX-M gene (458/620, 73.9%) were obtained from different individuals, and the most dominant genotype was CTX-M-9 group (303/458, 66.2%). The dominant species were Escherichia coli (E. coli; 403/458, 88.0%) and Klebsiella pneumoniae (K. pneumoniae; 26/458, 5.7%) among the isolates carrying CTX-M genes. All the CTX-M producers were resistant to ampicillin, cefazolin, cefuroxime, and ceftriaxone, but were all susceptible to biapenem, imipenem, and meropenem. The results of multivariate logistic regression model identified the enrollment in formal education (OR 2.321; 95% CI 1.302–3.768; P= 0.039), the hospitalization history within the last 6 months (OR 1.753; 95% CI 1.127–2.584; P= 0.031) and the antibiotics use within the last 6 months (OR 1.892; 95% CI 1.242–2.903; P= 0.034). The three variables were significantly associated with carriage of CTX-M ESBL producers (x2 = 21.21; df = 3; P< 0.001). The prevalence of fecal carriage of CTX-M ESBL-producing Enterobacteriaceae among healthy rural humans in Taian was high, and the recent antibiotic use and hospitalization history may be the important contributors.